The Development and Preliminary Testing of an Instrument for Assessing Fatigue Self-management Outcomes in Patients With Advanced Cancer. Issue 1 (January 2017) - Chan, Raymond Javan; Yates, Patsy; McCarthy, Alexandra L.
Abstract : Background: Fatigue is one of the most distressing and commonly experienced symptoms in patients with advanced cancer. Although the self-management (SM) of cancer-related symptoms has received increasing attention, no research instrument assessing fatigue SM outcomes for patients with advanced cancer is available. Objectives: The aim of this study was to describe the development and preliminary testing of an interviewer-administered instrument for assessing the frequency and perceived levels of effectiveness and self-efficacy associated with fatigue SM behaviors in patients with advanced cancer. Methods: The development and testing of the Self-efficacy in Managing Symptoms Scale–Fatigue Subscale for Patients With Advanced Cancer (SMSFS-A) involved a number of procedures: item generation using a comprehensive literature review and semistructured interviews, content validity evaluation using expert panel reviews, and face validity and test-retest reliability evaluation using pilot testing. Results: Initially, 23 items (22 specific behaviors with 1 global item) were generated from the literature review and semistructured interviews. After 2 rounds of expert panel review, the final scale was reduced to 17 items (16 behaviors with 1 global item). Participants in the pilot test (n = 10) confirmed that the questions in this scale were clear and easy to understand. Bland-Altman analysis showed agreement of results over a 1-week interval. Conclusions: The SMSFS-A items were generated using multiple sources. This tool demonstrated preliminary validity and reliability. Implications for Practice: The SMSFS-A has the potential to be used for clinical and research purposes. Nurses can use this instrument for collecting data to inform the initiation of appropriate fatigue SM support for this population.